The Influence of Instagram on Patient Visits Through Brand Awareness as a Mediating Variable: An Explanatory Sequential Mixed Method Study at Aqidah Hospital, Tangerang City - Vica Claudia Budiono; Dasrun Hidayat; Ign Wiseto P Agung (Training & Research Institute - Jeramba Ilmu Sukses, 2026)
Instagram has emerged as a crucial communication platform for hospitals to disseminate information and build community engagement. This study analyzes the influence of Instagram on patient visits, with brand awareness serving as a mediating variable at Aqidah Hospital in Tangerang City. The research employed a mixed methods approach with an explanatory sequential design. The quantitative phase involved 70 respondents, while the qualitative phase consisted of six informants engaged in social media management and hospital services. Results reveal that Instagram significantly influences brand awareness (p < 0.001) with R² = 0.750, indicating that 75% of brand awareness variance is explained by Instagram usage. Instagram also demonstrates a significant direct effect on patient visits (p < 0.001). Brand awareness significantly affects patient visits and mediates the relationship between Instagram and patient visits with an indirect effect of 0.319 (95% CI [0.177-0.493]). Qualitative findings reinforce quantitative results, indicating that Aqidah Hospital's Instagram content including health education, service information, facility visuals, and consistent branding enhances public recognition and encourages visiting intentions. This study underscores that Instagram functions not only as a promotional tool but also plays a pivotal role in shaping brand awareness, ultimately contributing to increased patient visits at Aqidah Hospital.